PRODUCT CHOICE ATTITUDE FORMATION: IT IS A MATTER OF A COLLECTIVE OR PERSONAL IDENTITY? - Irini, Rigopoulou; John, Kehagias; Athina, Chiladaki (European Scientific Journal, ESJ, 2015)
So far, specific social factors have been recognised as having a strong impact on the formation of consumer attitudes towards foreign products. At the same time, it has been argued that there is a need to explore other parameters that may affect the product choice attitude formation. In this context, this article explores cultural aspects that are associated with both, the collective and the personal identity of individuals by investigating whether and to what extent these aspects influence overall foreign product openness. The results allow us to argue that cultural aspects related to the collective identity have a significant impact on attitudes towards foreign products, while other aspects, related to the personal identity of individuals, seem to affect this attitude formation to a lesser extent .